To Divest or not to Divest? Social Assets in Russian Firms - Tuuli Juurikkala; Olga Lazareva (European Regional Science Association (ERSA), 2004)
In the planned economy firms were made responsible for providing their workers with social services, such as housing, day care and medical care. In the transforming Russia of the 1990s, social assets were to be transferred from industrial enterprises to the public sector. A law on divestment was put into force but it provided mostly general principles. Thus, for a period of several years, property rights over a major part of social assets, most notably housing, were not properly defined as the transfer decisions were largely left for the local level players to make. Strikingly, the time when assets were divested varied considerably across firms. In this paper we take a political economy approach and utilize recent survey data from 404 medium and large industrial enterprises in 40 Russian regions to study the effects different forms of bargaining between the firm and the municipality may have on the timing decisions. In particular, we apply survival data analysis to explore the determinants of the divestiture timing. Our results show that the firms which divested assets later receive more benefits from the local authorities, especially in places where there are more benefits to extract (i.e. the local budget is richer). Further, we find evidence that the firms which transferred assets later performed relatively worse in 2002 in terms of profitability, productivity and investments. Finally, the data shows that poorly defined property rights have an adverse effect on the incentives to invest in social assets, and hence on the quality of public service provision.
Keywords: 330